A high risk unstable case of left main bifurcation lesion treated with simultaneous kissing stents as salvage procedure - Kunwar, Brajesh Kumar; Pawar, Vikrant; Villkhoo, Ravneet Singh; Mishra, Shivram (International Journal of Research in Medical Sciences, 2020)
Bifurcation treatment with percutaneous coronary intervention is still one challenging task especially the left main bifurcation. And it becomes still more challenging when it is done in emergency situation in a very unstable patients. There are many one-stent and two-stent approaches available to treat the bifurcation lesions but no approach has proven superior to other. Here, we present a case of a 78-year-old male diagnosed with distal left main bifurcation lesion treated with simultaneous kissing stents technique presented with acute coronary syndrome, non-ST elevation myocardial infarction with pulmonary oedema in cardiogenic shock.